El interés superior del niño en las adopciones homoparentales - Sangalli, Marianela Noel (2014)
For this paper, we intended to analyze the possibility for same sex couples\nto adopt children. Despite there not being any legal impediment, our objective was to\nstudy it from the point of view of the best interest of the child.\nThrough a research of current legislation, both national and international, as well as\ndifferent legal doctrine articles and interviews we conducted, we attempt to express\nthe diverse visions about this issue, something we thought would be a very interesting\nthing to do in these days where many old paradigms are making room for new ones.\nStarting from the definition of concepts such as ?family? and ?best interest of the\nchild?, we intend to provide a broad view of different matters at stake regarding such\na current topic